(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
Nowadays, the urgency of searching for new forms of building effective personnel management systems, including those related to the individualization of psychosomatic characteristics of the individual, the individual team, and the organization as a whole, does not fade. The article considers the possibility of using the theory of elements to build an optimal system of personnel management in an organization. This, of course, can affect the effectiveness of employees in the organization, as well as its development.